Decreasing Child Sex Ratio in Jammu and Kashmir: A Serious Social Problem - Jasrotia, Rakesh; Singh, Sarvjeet (National Geographical Journal of India, 2022)
The imbalanced sex ratio of the population in Jammu and Kashmir has become a serious problem, for the society. In recent decade more male babies have been born in state due to people’s preference for having male children. The phenomena of sex determination and sex selective abortion is now concentrating not only in towns and cities but also approaching in rural areas with the availability of better road and transport facilities. The findings of this paper reveal that in spite of the various legal provisions and women’s specific developmental programs, the gender bias and deep-rooted prejudices still persist. The most influential factor that has affected the sex ratio in the state is a strong son preference. With this view in mind, the present paper aims to identify how different forces of social change are responsible for the problem of declining sex ratio. Paper also looks into the different concepts of sex ratio and concludes with some suggestions, which can be utilized for solving the problem of declining child sex ratio